American rebel [compact disc, unabridged] : the life of Clint Eastwood - Eliot, Marc (Tantor Audio, 2009)
In American Rebel, Marc Eliot examines the ever-exciting, often tumultuous arc of Clint Eastwood's life and career, from his days as a disaffected college dropout to his rise to fame as the archetypal loner to his acceptance into the pantheon as a multiple Academy Award winner.